Analisis Pemanfatan Pemodelan Data Mining untuk Pola Permainan Timnas Sepakbola - Ardiantoro, Luki; Ristono, Joko (DPPM Universitas Pelita Bangsa, 2024)
Football is a sport that has a very complex variety of tactics, strategies and formations. In this study, the researcher observed and studied the game patterns, tactics and game strategies applied by the Indonesian men's national football team. The methods used are the FP-Tree algorithm and FP-Growth Data Mining to learn the tactical patterns used in the match. Data is collected from a variety of secondary sources, the internet, and match recordings. The purpose of the research is to model the national team's game activities to be simulated with a data mining algorithm, so that competitive game level standards are obtained from national teams that are able to compete at the Asian level. This can be the standard for the quality of performance and coaches of the national team in the next era. The result obtained is that the data mining algorithm can be used to analyze the game pattern of a football team